Angiogenesis: Mechanical Cues Regulating Proangiogenic Potential of Human Mesenchymal Stem Cells through YAP‐Mediated Mechanosensing (Small 25/2020). Issue 25 (25th June 2020) - Bandaru, Praveen; Cefaloni, Giorgia; Vajhadin, Fereshteh; Lee, KangJu; Kim, Han‐Jun; Cho, Hyun‐Jong; Hartel, Martin C.; Zhang, Shiming; Sun, Wujin; Goudie, Marcus J.; Ahadian, Samad; Dokmeci, Mehmet Remzi; et al.
Abstract : In article number 2001837, Junmin Lee, Ali Khademhosseini, and co‐workers develop a bioreactor‐based platform to investigate the effect of human mesenchymal stem cell (hMSC) culture microenvironments including matrix rigidity and dynamic mechanical compression on their secretion level of pro‐angiogenic factors. It is demonstrated that these mechanical cues regulate pro‐angiogenic potential of hMSCs through yes‐associated protein (YAP)‐mediated mechanosensing.